Karakterisasi Parsial Streptomyces spp., Agens Pengendali Hayati Peyakit Lincat Tembakau - Triwidodo Arwiyanto; Ari Astuti; Y. M. S. Maryudani (Jurnal Perlindungan Tanaman Indonesia, 2007)
Local isolates of Streptomyces spp. were proven could suppress "lincat disease" of tobacco in the field. Six isolates were chosen for partial characterization of their bacteriological properties as based for the next experiments purposes. The results indicated that the isolates produce miselium with spore chains, gram positive, aerob, catalase and oxidase positive. The isolates also hydrolize starch, gelatine and esculine; produce lecithinase enzyme, reduce nitrate to nitrite, do not produce melanine pigment, did not produce hydrogen sulfide. The isolates were sensitive against streptomycine and rifampicin; able to use several carbon and nitrogen sources tested. Capable to grow on several medium pH, from 4,3 to 8,0. The isolates were able to grow from 5° C to 45° C; able to grow on medium containing 4% to 7% NaCl and ion the medium containing 0,1% of phenol. Plant pathogenicity test result showed negative responses which indicated that the used isolates were non plant pathogenic. The ability in suppressing lincat pathogen (Ralstonia solanacearum and Meloidogyne incognita) in vitro was vary between isolates.